Abomasal ulcers in cattle. (2nd November 2021) - Turner, Andrea
Abstract : Abomasal ulcers in cattle often present with non-specific clinical signs meaning that it is one of several differentials that may be relevant for a wide range of clinical presentations. This, combined with a lack of accurate diagnostic tests, makes the condition hard for the clinician to diagnose with confidence. The management and prognosis for cattle differ significantly depending on the severity and chronicity of an abomasal ulcer. It is important that clinicians are aware of the possibilities for diagnosis, treatment, and prognosis of the varying forms of this condition so they can offer the most appropriate management plans for the individual animal in every case.